1986
DOI: 10.1007/bf00178509
|View full text |Cite
|
Sign up to set email alerts
|

Associative factors in the effects of morphine on self-stimulation

Abstract: These experiments tested the hypothesis that the suppressing and facilitating effects of morphine on intracranial self-stimulation (ICS) (measured 1 h and 3 h post-injection, respectively) are influenced by associative, non-pharmacological factors. Experiment 1 confirmed previous demonstrations that the facilitation of ICS by morphine (10 mg/kg) develops with repeated drug exposures. Once ICS facilitation had developed, the effect was mimicked by saline injection in most subjects. In a separate group of animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…However, Eikelboom and Stewart (1979) were unable to replicate this latter result. In addition, Hand and Franklin (1986) found that after several pairings of morphine and self-stimulation, the resuiting facilitation of this behavior was not consistently antagonized by naloxone, and hence unlikely to be opiate receptor mediated. The present data support their proposal that the reinforcing effects of opioids expressed in drug-free animals are mediated by an unidentified non-opioid mechanism, and argue strongly against the hypothesis that the conditioned effects of opioids are related to endogenous opioid activity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, Eikelboom and Stewart (1979) were unable to replicate this latter result. In addition, Hand and Franklin (1986) found that after several pairings of morphine and self-stimulation, the resuiting facilitation of this behavior was not consistently antagonized by naloxone, and hence unlikely to be opiate receptor mediated. The present data support their proposal that the reinforcing effects of opioids expressed in drug-free animals are mediated by an unidentified non-opioid mechanism, and argue strongly against the hypothesis that the conditioned effects of opioids are related to endogenous opioid activity.…”
Section: Discussionmentioning
confidence: 95%
“…This dissociation of mechanisms underlying acquisition and expression of drug effects on behavior is evident in a wide variety of pharmacological studies (Robertson et al 1982;Beninger and Hahn 1983;Hand and Franklin 1986;Snodgrass and Allen 1988), and suggests that the neural mechanisms underlying acquisition of certain behaviors are generally not recruited when the behavior is expressed. Nor may acquisition-related events even be involved in the retention of these behaviors over long periods of time.…”
Section: Discussionmentioning
confidence: 96%
“…It has also been shown that the most effective site to alter reward threshold with ICSS is in the medial forebrain bundle (MFB). Morphine (Hand & Franklin, 1986) and cocaine (Mague, Andersen, & Carlezon, 2005) administration potentiates ICSS responding in adult animals. Interestingly, our prenatal morphine exposure, on gestation Days 11-18, also enhances ICSS in the presence of a single 5 mg/kg cocaine injection in adult male rats (Vathy, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the dissociation of mechanisms underlying acquisition and expression of drug effects on behaviour is evident in a wide variety of pharmacological studies (Robertson et al, 1982;Beninger & Hahn 1983;Hand & Franklin 1986;Snodgrass & Allen 1988), and presumably the expression of morphine reward attributes to unidentified mechanisms rather than the traditional reward circuit.…”
Section: Discussionmentioning
confidence: 99%